La question de l’efficience d’un enseignant débutant en classe - Sophie Baconnet (Éducation et Socialisation)
The article questions of the process of development of competences in the teaching profession. It studies the linguistic didactic gestures of a trainee, observed within the setting up of an innovative teacher training. This innovative plan gives second year teacher students the responsability of the class once a week all year long, throughout coached writing exercise. In this article, we assume that teacher efficency come through his ability to move all the pupils forward, while keeping an eye on each one. The research method is a clinical analysis focusing on one case, completed by the analysis of the verbal and behavioural elements included in the interviews. The study exposes two particular cases, showing a significant difference between a backward pupil and a pupil ahead of his class. Two extracts of the verbatims of writing sessions in first year infant class are analysed in order to set forth the crucial part of language in the joint development of competences in the teacher and the pupils. The results show how the teacher fits each of the pupils speech. The teacher language adressed in the classroom aims to erase variations between pupils. There the language is considered as the main instrument of the professional development observed. The didactic gestures are laid out as revealing professional competences in the process of being acquired.